Maksimalisasi Keuntungan pada Bisnis “Naya Online Shopping” dengan Metode Simpleks - Diva Nadhofah Sadarisma; A. Rama El Shinta; Zulfa Nabila Kulsum; Dedek Kustiawati (Publikasi Indonesia, 2022)
Linear programming is one of the most widely used operations research techniques in practice and is known for being easy to understand. The method for completing the linear program in the